2014
DOI: 10.3109/01902148.2014.983282
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary preconditioning, injury, and inflammation modulate expression of the candidate tumor suppressor geneECRG4in lung

Abstract: Purpose The human c2orf40 gene encodes a candidate tumor suppressor called Esophageal Cancer-Related Gene-4 (ECRG4) that is a cytokine-like epigenetically-regulated protein that is characteristically downregulated in cancer, injury, inflammation, and infection. Here, we asked whether ECRG4 gene expression is detectable in lung epithelial cells and if its expression changes with inflammation, infection, and/or protective preconditioning. Materials and Methods We used immunoblotting, PCR, and quantitative PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The NR8383 cells were stimulated with ML exosomes or PBS for 6 or 12 h, and total RNA was extracted using Trizol regent (Thermo Fisher Scientific). RNA concentrations and quality were determined by Nanodrop 2000 (Thermo Fisher Scientific), and 1 mg was reverse-transcribed using the iScript cDNA synthesis kit (Bio-Rad) as previously described (22). cDNA was used to quantify gene expression by real-time quantitiative PCR (iQ5 cycler; Bio-Rad) in a 25-ml reaction containing 100 nM of primers and iQ SYBR Green Supermix (Bio-Rad).…”
Section: Real-time Quantitative Rt-pcrmentioning
confidence: 99%
“…The NR8383 cells were stimulated with ML exosomes or PBS for 6 or 12 h, and total RNA was extracted using Trizol regent (Thermo Fisher Scientific). RNA concentrations and quality were determined by Nanodrop 2000 (Thermo Fisher Scientific), and 1 mg was reverse-transcribed using the iScript cDNA synthesis kit (Bio-Rad) as previously described (22). cDNA was used to quantify gene expression by real-time quantitiative PCR (iQ5 cycler; Bio-Rad) in a 25-ml reaction containing 100 nM of primers and iQ SYBR Green Supermix (Bio-Rad).…”
Section: Real-time Quantitative Rt-pcrmentioning
confidence: 99%
“… 41 Decreased cell proliferation has been reported in human lung epithelial cells in response to ECRG4 over-expression. 16 …”
Section: Discussionmentioning
confidence: 99%
“… 6 Other authors have also recently reported ECRG4 full-length 14 kDa protein in mouse lung by immunoblotting and in type I alveolar cells by immunohistochemistry. 16 The aim of the present study was to analyse ECRG4 expression in a wide series of normal rat tissues by qPCR and immunohistochemistry, in order to establish its expression profiles in the rat. A detailed review of the available literature about ECRG4 functions has also been performed.…”
Section: Introductionmentioning
confidence: 99%
“…The C2ORF40 gene is important in processes associated with physiological functional regulation, including inflammation, injury, senescence, the neuroendocrines environment, differentiation and apoptosis (5)(6)(7)(8)(9)(10)(11)(12)(13). Notably, previous studies have indicated that C2ORF40 is a candidate tumor suppressor gene associated with prognosis in a variety of tumors (4,(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%